Transmembrane Domains of Highly Pathogenic Viral Fusion Proteins Exhibit Trimeric Association In Vitro - Webb, Stacy R. (mSphere, 2018)
Enveloped viruses require viral fusion proteins to promote fusion of the viral envelope with a target cell membrane. To drive fusion, these proteins undergo large conformational changes that must occur at the right place and at the right time. Understanding the elements which control the stability of the prefusion state and the initiation of conformational changes is key to understanding the function of these important proteins. The construction of mutations in the fusion protein transmembrane domains (TMDs) or the replacement of these domains with lipid anchors has implicated the TMD in the fusion process. However, the structural and molecular details of the role of the TMD in these fusion events remain unclear. Previously, we demonstrated that isolated paramyxovirus fusion protein TMDs associate in a monomer-trimer equilibrium, using sedimentation equilibrium analytical ultracentrifugation. Using a similar approach, the work presented here indicates that trimeric interactions also occur between the fusion protein TMDs of Ebola virus, influenza virus, severe acute respiratory syndrome coronavirus (SARS CoV), and rabies virus. Our results suggest that TM-TM interactions are important in the fusion protein function of diverse viral families. IMPORTANCE Many important human pathogens are enveloped viruses that utilize membrane-bound glycoproteins to mediate viral entry. Factors that contribute to the stability of these glycoproteins have been identified in the ectodomain of several viral fusion proteins, including residues within the soluble ectodomain. Although it is often thought to simply act as an anchor, the transmembrane domain of viral fusion proteins has been implicated in protein stability and function as well. Here, using a biophysical approach, we demonstrated that the fusion protein transmembrane domains of several deadly pathogens—Ebola virus, influenza virus, SARS CoV, and rabies virus—self-associate. This observation across various viral families suggests that transmembrane domain interactions may be broadly relevant and serve as a new target for therapeutic development.